UTILIZING DIGITAL MEDIA TO ENHANCE STUDENTS’ TOEFL LISTENING SKILLS - Radhiyani, Fitri; Yusuf, Rudy; Rahim, Ismail; Mustikawati, Yunitari; Burhamzah, Rahmita (PEDAMAS (PENGABDIAN KEPADA MASYARAKAT), 2025)
This community service activity aims to improve students’ TOEFL listening skills through the use of digital media. The program involved third-semester students enrolled in the Extensive Listening course at the English Education Department. The service was carried out through several stages: a preliminary needs analysis, implementation of digital media-based listening activities (including TOEFL practice applications, YouTube academic channels, and online audio-based quizzes), and a post-test. The results indicate significant improvement in students’ TOEFL listening performance and increased motivation and engagement in using digital media as a learning tool. These findings demonstrate that digital media can serve as an effective and accessible platform to enhance TOEFL listening preparation among university students. Keywords: Digital Media, TOEFL, Listening, English Education, Students